LEFT-WING POPULISM? THE CASE OF LATIN AMERICA - Zanatta, Loris (2018)
Latin American is commonly distinguished from European populism, the former being left-wing, the latter right. But such categorization fails to do justice to a complex phenomenon. With other forms of populism, the Latin American brand shares redemptive zeal and dreams of a unanimous utopia – it response to the disruption of political order and social ties. But the concept of ‘people’ that populism set out to regenerate differs from case to case and the kind of past it evokes: while people, for the United States, must entail a constitutional charter so that US populism develops within the bounds of liberal democracy, Latin American populism conjures up a holistic natural group, the people as an organic community underlying political regimes that are against the ethos and institutional structure of liberal democracy. Springing from an age-old organic and quasireligious vision, Latin American populism proclaims the principle of unanimity. It is inclusive, but may turn totalitarian in the people’s name. It may have a popular basis and implement policies of social distributism, but its outstanding feature is the ambition to transform its people into the whole people. In refusing to be part of a plural group, and in claiming to embody the only legitimate people, it thus ends up having to play all the roles that are shared out among left- and right-wing parties in a pluralist system.